1996
DOI: 10.1021/tx9501795
|View full text |Cite
|
Sign up to set email alerts
|

Improved Strategies for Postoligomerization Synthesis of Oligodeoxynucleotides Bearing Structurally Defined Adducts at the N2 Position of Deoxyguanosine

Abstract: Improved methodology has been developed for preparation of oligodeoxynucleotides bearing adducts on the N2 position of guanine in which the adduction reaction is carried out in homogeneous solution rather than while the oligonucleotide is immobilized on a solid matrix. The methodology utilizes a new synthon, 2-fluoro-O6-(trimethylsilylethyl)-2'-deoxyinosine (3). Nucleoside 3 is stable to the conditions of oligonucleotide synthesis, but the O6 protection is eliminated under very mild conditions following displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 31 publications
0
95
0
Order By: Relevance
“…Removal of the O 6 protecting group under acidic conditions yielded 29, which was oxidized to oligodeoxynucleotide 30. 47 Our post-synthetic modification strategy 48 allowed preparation of various dG enal adducts from a single modified phosphoramidite. A challenge was the preparation of stereochemically-defined amino diols for the crotonaldehyde (31,32) and 4-HNE adducts (33)(34)(35)(36) (Figure 2).…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
“…Removal of the O 6 protecting group under acidic conditions yielded 29, which was oxidized to oligodeoxynucleotide 30. 47 Our post-synthetic modification strategy 48 allowed preparation of various dG enal adducts from a single modified phosphoramidite. A challenge was the preparation of stereochemically-defined amino diols for the crotonaldehyde (31,32) and 4-HNE adducts (33)(34)(35)(36) (Figure 2).…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
“…(15) had observed more efficient coupling of 2-amino-2-phenylethanol with a fluorinated oligonucleotide after its cleavage from the support with NaOH as above, we subsequently observed that a separate NaOH cleavage step is not necessary with our less-hindered amine, because treatment (3 days at room temperature) of the glass beads with an aqueous solution of 0.9 M bis(3-aminopropyl)disulfide dihydrochloride and 4.5 M Et 3 N completely cleaves the oligonucleotide from the support concomitantly with replacement of the fluorine. The oligonucleotide, *20-Pri-C3, was purified by HPLC on the Hamilton column as above (t R , 15 min).…”
Section: Bis[(n-tert-butyloxycarbonyl)-3-aminopropyl]disulfide-mentioning
confidence: 99%
“…Phosphoramidite reagents containing the required "activated" O 6 -(2-(trimethylsilylethyl)-2-fluorohypoxanthine (2) and 6-chloropurine (3) bases have been previously synthesized and incorporated in oligonucleotides via standard solid-phase methods (25,(34)(35)(36). The sitespecific synthesis of an M 1 dG-adducted oligonucleotide is shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%